2016
DOI: 10.18632/oncotarget.9246
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial ovarian cancer-secreted exosomal miR-222-3p induces polarization of tumor-associated macrophages

Abstract: Cancer secreted exosomal miRNAs are emerging as mediators between tumor-stoma crosstalk. Here, we show epithelial ovarian cancer (EOC)-derived exosomes activated macrophages to a tumor-associated macrophage (TAM)-like phenotype with SOCS3/STAT3 pathway involvement, which could facilitate the progression of cancer. MiR-222-3p was enrichment in exosomes released from EOC cells and it could be transferred to macrophages. Overexpression of miR-222-3p in macrophages induced polarization of the M2 phenotype. Lucifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
221
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(226 citation statements)
references
References 37 publications
4
221
0
1
Order By: Relevance
“…Abundant M2-like TAMs in the tumor microenvironment promote carcinogenesis by inducing angiogenesis, suppressing anti-cancer immune response, and antagonizing cancer cell apoptosis [143]. Epithelial ovarian cancer cells induced the polarization of TMAs toward M2-like phenotype via secreting exosomal miR-222-3p and miR-940 [127,128]. Besides, under hypoxic condition, epithelial ovarian cancer cell-secreted exosomes contained miRNAs such as miR-21-3p, miR-125b-5p, and miR-181d-5p, which enhanced the polarization of M2-like TAMs and promoted cancer growth [129].…”
Section: Cancer-derived Exosomal Mirnas and Tamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abundant M2-like TAMs in the tumor microenvironment promote carcinogenesis by inducing angiogenesis, suppressing anti-cancer immune response, and antagonizing cancer cell apoptosis [143]. Epithelial ovarian cancer cells induced the polarization of TMAs toward M2-like phenotype via secreting exosomal miR-222-3p and miR-940 [127,128]. Besides, under hypoxic condition, epithelial ovarian cancer cell-secreted exosomes contained miRNAs such as miR-21-3p, miR-125b-5p, and miR-181d-5p, which enhanced the polarization of M2-like TAMs and promoted cancer growth [129].…”
Section: Cancer-derived Exosomal Mirnas and Tamsmentioning
confidence: 99%
“…Immunosuppressive [125] miR-24-3p NPC Immunosuppressive [126] miR-891a NPC Immunosuppressive [126] miR-106a-5p NPC Immunosuppressive [126] miR-20a-5p NPC Immunosuppressive [126] miR-1908 NPC Immunosuppressive [126] TAMs miR-222-3p EOC Immunosuppressive [127] miR-940 EOC Immunosuppressive [128] miR-21-3p EOC Immunosuppressive [129] miR-125b-5p EOC Immunosuppressive [129] miR-181d-5p EOC Immunosuppressive [129] miR-21 Head and neck cancer Immunosuppressive [130] miR-1246 Colon cancer Immunosuppressive [131] miR-16 Breast cancer Immunostimulatory [132] MDSCs miR-107 Gastric cancer Immunosuppressive [133] miR-21 OSCC Immunosuppressive [134] miR-21 Glioma Immunosuppressive [135] miR-10a Glioma Immunosuppressive [135] miR-29a Glioma Immunosuppressive [136] miR-92a Glioma Immunosuppressive [136] miR-155 CLL Immunosuppressive [137] CAFs miR-27a Gastric cancer Immunosuppressive [138] miR-1247-3p HCC Immunosuppressive [139] miR-21 HCC Immunosuppressive [140] NPC nasopharyngeal carcinoma, TAM tumor-associated macrophage, EOC epithelial ovarian cancer, MDSC myeloid-derived suppressor cell, OSCC oral squamous cell carcinoma, CLL chronic lymphocytic leukemia, CAF cancer-associated fibroblast, HCC hepatocellular carcinoma M2-like phenotype and suppressing the expression of M1 phenotype-associated markers [130]. Similarly, Cooks et al observed that cancer cells harboring TP53 mutation could reprogram neighboring TAMs into pro-tumor state via secreting miR-1246-enriched exosomes [131].…”
Section: Effector T Cells Mir-690 Melanomamentioning
confidence: 99%
“…A plenty of studies have proven the exosome mediated functional shuttling of miRNA in multiple cell types . For example, the uptake of miR‐222‐3p enriched exosomes by macrophages, released from ovarian cancer cells, led to stimulation of the STAT3 pathway which in turn promotes macrophage activation . Likewise, exosomal miRNA cargos were found to be delivered from ependymal cells into the brain by crossing the blood brain barrier, triggering downregulation of miRNA specific target genes .…”
Section: Alternative Routes For Intercellular Mirna Exchangementioning
confidence: 99%
“…A recent study established the role of EOC-derived exosomes in mediating the activation of macrophages to a tumour-associated macrophage (TAM) state [94]. They also demonstrated that SKOV-3 cells when grown with conditioned media from the transformed macrophages were more likely to migrate and proliferate.…”
Section: New Approaches To Elucidate the Role Of Exosomes In Cancermentioning
confidence: 98%